2018
DOI: 10.1016/j.lwt.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan on thermal, microstructural and rheological properties of rice and wheat flours-based batters

Abstract: Wheat flour replacement by rice flour is a key strategy in gluten-free batter production. Rice flour needs hydrocolloids to offset the development of the network of the mix. In this context, the aim of this work was to analyze the influence of chitosan (0 to 1 g/100 g of batter) addition on the microstructural, rheological and thermal properties of wheat:rice flours batters (100:0; 70:30, 30:70 and 0:100 (g/g)). Results showed that increasing replacement of wheat flour by rice one decreased the consistency (K)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…The increase of the dispersion viscosity is an indication of forming a network structure within the dispersion. The charged nature of chitosan (positive due to nitrogen bonding) is noted to cause the viscosity to increase, which was observed in other systems like kaolin [ 60 ] and rice flour formulation [ 46 ], where chitosan addition considerably increased the viscosity of both materials. At the conditions used in this study, it is expected that the chitosan is adsorbed on bentonite particles via hydrogen bonding of carbonyl and/or hydroxyl groups from chitosan macromolecules to hydroxyl groups present on the surface of bentonite, as well as via electrostatic interactions between groups from chitosan and negative sites present on the surface of bentonite.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The increase of the dispersion viscosity is an indication of forming a network structure within the dispersion. The charged nature of chitosan (positive due to nitrogen bonding) is noted to cause the viscosity to increase, which was observed in other systems like kaolin [ 60 ] and rice flour formulation [ 46 ], where chitosan addition considerably increased the viscosity of both materials. At the conditions used in this study, it is expected that the chitosan is adsorbed on bentonite particles via hydrogen bonding of carbonyl and/or hydroxyl groups from chitosan macromolecules to hydroxyl groups present on the surface of bentonite, as well as via electrostatic interactions between groups from chitosan and negative sites present on the surface of bentonite.…”
Section: Resultsmentioning
confidence: 85%
“…However, the poor solubility of chitin is the major limiting factor in its utilization and the investigation of its properties and structure [ 43 ]. Important properties of chitosan include solubility in various media, high viscosity, polyelectrolyte behavior, polyoxysalt formation, the ability to form films, metal chelations, optical, and structural characteristics [ 44 ] and applications are including but not limited to cosmetics, water engineering, textile industry, food processing, agriculture, chromatographic separations, solid state batteries, biomedical applications such as tissue engineering, and even photography [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result was agreed with the findings of Sansano et al . (), who reported that the incorporation of chitosan decreased the T m of rice dough. In addition, the T m clearly increased with the storage time, with ranges of 0.25–1.61 °C and 0.41–2.14 °C for 14 and 30 days respectively.…”
Section: Resultsmentioning
confidence: 95%
“…The gelatinisation properties were determined with the method of Sansano et al (2018). The frozen samples were thawed until the core temperature of the samples reached to 20°C, and the measured procedure was from 20 to 100°C at 10°C min À1 .…”
Section: Analysis Of Water State and Thermal Properties In Fast Frozementioning
confidence: 99%
“…The presence of sugar, oil, salt and HPMC in the dough also could have had influence in the gelatinization and retrogradation of starch because they can restrict granules from swelling (Villanueva et al, 2018). A strong interaction between hydrocolloids and starch that induces the formation of a stable structure that makes starch require higher temperatures to start its gelatinization has been reported (Sansano et al, 2018). Neither the gelatinization nor the retrogradation thermograms included the amylose-lipid complex dissociation peak, unlike was observed by when measured tef flour.…”
Section: Thermal Properties Of Doughsmentioning
confidence: 95%